2021
DOI: 10.3390/ijerph18062995
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ginger Root Powder Dietary Supplement on Productive Performance, Egg Quality, Antioxidant Status and Blood Parameters in Laying Japanese Quails

Abstract: Medicinal plants with antibacterial effects have been used by humans for centuries. In the recent decade, due to the development of antibiotic resistant strains, many studies have focused on the use of natural compounds as feed additives in livestock. Ginger, among all, have repetitively shown numerous biological activities, antibacterial, and antibiotic properties. This study was conducted to evaluate the effects of ginger root powder (GP) on the performance, egg quality, and blood parameters of Japanese quai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
1
12
1
1
Order By: Relevance
“…In contrast, Ayed [36] did not find significant differences in the addition of garlic cloves in feed in response to productive parameters such as production and egg weight; however, with 500 g/Ton it obtained a yolk color of 7.06. The inclusion of a phytobiotic mixture of garlic and ginger at a dose greater than 7.5 g/kg improved the feed conversion, and at a dose of 12.5 g/kg, increased the Haugh units [42]; meanwhile, the addition of Allium sativum in the feed of laying hens did not show improvements in production index and Haugh units. However, there were improvements in daily egg production, egg weight, and shell thickness [34].…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, Ayed [36] did not find significant differences in the addition of garlic cloves in feed in response to productive parameters such as production and egg weight; however, with 500 g/Ton it obtained a yolk color of 7.06. The inclusion of a phytobiotic mixture of garlic and ginger at a dose greater than 7.5 g/kg improved the feed conversion, and at a dose of 12.5 g/kg, increased the Haugh units [42]; meanwhile, the addition of Allium sativum in the feed of laying hens did not show improvements in production index and Haugh units. However, there were improvements in daily egg production, egg weight, and shell thickness [34].…”
Section: Discussionmentioning
confidence: 90%
“…In this study, ginger and cinnamon, administrated separately or together, significantly increased the TAC in diabetic rats. In previous studies, ginger-induced improvement in diabetes patients and experimental animals was explained by the powerful scavenging effect of free radicals induced by active constituents of ginger like gingerol, vallinoids, paradol, and zingerone ( El-Ghawet et al, 2019 ; Nemati et al, 2021 ). Cinnamon also has potent antioxidant activities because it is rich in procyanidins and catechins, which reduce oxidative stress and prevent β-cell damage, and this may be explain the anti-diabetic activity of cinnamon ( Al-Waili et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by a previous study which revealed that Eugenol, one of the compounds that exist in cinnamon, improves the symptoms of the neurodegenerative diseases such as Alzheimer, Parkinson, and depression and increases the expression of neurotropic factors in the hippocampus that lead to brain cell regeneration ( Aryanezhad et al, 2021 ). Regarding ginger, it contains a different phenolic component, and it exhibited many bioactivities such as antioxidant and anti-anxiety ( Nemati et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, according to experiments, studies, and applications of traditional medicine and physiotherapy, it is possible to get more benefits for ginger, whether by eating boiled or oil or powder use or in other ways (11) . The avoidance of oxidative stress and liver toxicity by ginger can be linked to its antioxidants (12) .…”
Section: Introductionmentioning
confidence: 99%